Occludin regulates glucose uptake and ATP production in pericytes by influencing AMP-activated protein kinase activity. Issue 2 (February 2018) - Castro, Victor; Skowronska, Marta; Lombardi, Jorge; He, Jane; Seth, Neil; Velichkovska, Martina; Toborek, Michal
Energetic regulation at the blood-brain barrier is critical for maintaining its integrity, transport capabilities, and brain demands for glucose. However, the underlying mechanisms that regulate these processes are still poorly explored. We recently characterized the protein occludin as a NADH oxidase and demonstrated its influence on the expression and activation of the histone deacetylase SIRT-1. Because SIRT-1 works in concert with AMP-activated protein kinase (AMPK) (AMPK), we investigated the impact of occludin on this metabolic switch. Here we show that in blood-brain barrier pericytes, occludin promotes AMPK expression and activation, influencing the expression of glucose transporters GLUT-1 and GLUT-4, glucose uptake, and ATP content. Furthermore, occludin expression, AMP-dependent protein kinase activity, and glucose uptake were altered under inflammatory (TNFα) and infectious (HIV) conditions. We also show that pericytes share glucose and mitochondria with astrocytes, and that occludin levels modify the ability of pericytes to share those energetic resources. In addition, we demonstrate that murine mitochondria can be transferred from live brain microvessels to energetically impaired human astrocytes, promoting their survival. Our findings demonstrate that occludin plays an important role in blood-brain barrier pericyte metabolism by influencing AMPK protein kinase activity, glucose uptake, ATP production, and by regulating the ability of pericytes to interact metabolically with astrocytes.